Megalosauripus transjuranicus ichnosp. nov. A new Late Jurassic theropod ichnotaxon from NW Switzerland and implications for tridactyl dinosaur ichnology and ichnotaxomy - Razzolini, Novella L. (PLoS One, 2017)
A new ichnospecies of a large theropod dinosaur, Megalosauripus transjuranicus, is described from the Reuchenette Formation (Early–Late Kimmeridgian, Late Jurassic) of NW Switzerland. It is based on very well-preserved and morphologically-distinct tracks (impressions) and several trackways, including different preservational types from different tracksites and horizons. All trackways were excavated along federal Highway A16 near Courtedoux (Canton Jura) and systematically documented in the field including orthophotos and laserscans. The best-preserved tracks were recovered and additional tracks were casted. Megalosauripus transjuranicus is characterized by tridactyl tracks with clear claw and digital pad impressions, and notably an exceptionally large and round first phalangeal pad on the fourth digit (PIV1) that is connected to digit IV and forms the round heel area. Due to this combination of features, M. transjuranicus clearly is of theropod (and not ornithopod) origin. M. transjuranicus is compared to other Megalosauripus tracks and similar ichnotaxa and other unassigned tracks from the Early Jurassic to Early Cretaceous. It is clearly different from other ichnogenera assigned to large theropods such as Eubrontes–Grallator from the Late Triassic and Early Jurassic or Megalosauripus–Megalosauropus–Bueckeburgichnus and Therangospodus tracks from the Late Jurassic and Early Cretaceous. A second tridactyl morphotype (called Morphotype II) is different from Megalosauripus transjuranicus in being subsymmetric, longer than wide (sometimes almost as wide as long), with blunt toe impressions and no evidence for discrete phalangeal pad and claw marks. Some Morphotype II tracks are found in trackways that are assigned to M. transjuranicus, to M.? transjuranicus or M. cf. transjuranicus indicating that some Morphotype II tracks are intra-trackway preservational variants of a morphological continuum of Megalosauripus transjuranicus. On the other hand, several up to 40 steps long trackways very consistently present Morphotype II features (notably blunt digits) and do not exhibit any of the features that are typical for Megalosauripus (notably phalangeal pads). Therefore, it is not very likely that these tracks are preservational variants of Megalosauripus transjuranicus or Megalosauripus isp. These trackways are interpreted to have been left by an ornithopod dinosaur. The high frequency of large theropod tracks in tidal-flat deposits of the Jura carbonate platform, associated on single ichnoassemblages with minute to medium-sized tridactyl and tiny to large sauropod tracks has important implications for the dinosaur community and for paleoenvironmental and paleogeographical reconstructions. As with most other known occurrences of Megalosauripus tracks, M. transjuranicus is found in coastal settings, which may reflect the preference of their theropod trackmakers for expanded carbonate flats where food was abundant.